2016
DOI: 10.1111/ajt.13558
|View full text |Cite
|
Sign up to set email alerts
|

EBV-Positive and EBV-Negative Posttransplant Diffuse Large B Cell Lymphomas Have Distinct Genomic and Transcriptomic Features

Abstract: The molecular pathogenesis of posttransplant diffuse large B cell lymphoma (PT‐DLBCL) is largely unknown. We have recently shown that Epstein‐Barr virus–positive (EBV+) and –negative (EBV−) PT‐DLBCL have distinct gene expression profiles, and the transcriptomic profile of EBV− PT‐DLBCL is similar to that of DLBCL in immunocompetent individuals (IC‐DLBCL). To validate these observations at the genomic level, we performed array–comparative genome hybridization (aCGH) analysis of 21 EBV+ PT‐DLBCL, 6 EBV− PT‐DLBCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 36 publications
5
42
0
Order By: Relevance
“…It has been postulated that EBV-negative PTLD represents a distinct entity [5, 8]. In support of this hypothesis, gene expression profiling studies have revealed clear differences between EBV-positive and EBV-negative PTLDs [10, 18]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that EBV-negative PTLD represents a distinct entity [5, 8]. In support of this hypothesis, gene expression profiling studies have revealed clear differences between EBV-positive and EBV-negative PTLDs [10, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of non-EBV-related PTLD may be similar to non-Hodgkin's lymphomas (NHL) [6]. EBV-negative PTLD has been proposed to be a distinct entity and typically presents as a late complication of transplantation with a median of 50–60 months [5, 710]. EBV-negative PTLDs typically display monomorphic morphology [1].…”
Section: Introductionmentioning
confidence: 99%
“…Other potential risks for PTLD may include issues related to alternative donors and alternative GVHD prophylaxis and donor/recipient EBV serostatus. For EBV serostatus, there may be a higher risk of developing PTLD in EBV‐positive recipients receiving cells from EBV‐seronegative donors since it is much harder to generate a primary immune response to EBV reactivation post‐alloHCT . For our cohort, EBV‐negative donors were used in 53 EBV‐positive recipients and 43 developed EBV pos PTLD with the remainder developing EBV neg PTLD.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of PD-L1 expression has been examined in EBV+ B cells and it may have both viral and genetic components. Green et al, (77) identified an AP-1 responsive element in the PD-L1 gene and showed the EBV protein LMP1 can increase PD-L1 expression via the JAK/STAT pathway while a gain/amplification of chromosomal region 9p24.1, which includes the PD-L1 and PD-L2 genes, was found in 2 of 5 clinical EBV+ B cell PTLD specimens in another study (78). Collectively, these results suggest that inhibitory pathways may play an important role in impaired T cell responses in PTLD.…”
Section: The Immune Response To Ebv In Transplant Recipients and In Ptldmentioning
confidence: 99%